Investigation of Langmuir, Freundlich and Temkin Adsorption Isotherm of Tramadol by Multi-Wall Carbon Nanotube - Vadi, Mehdi; Omidi Mansoorabad, Asma; Mohammadi, Majid; Rostami, Nasrin (Asian Journal of Chemistry, 2013)
In this experimental research the adsorption of the isotherm of tramadolas, a kind of narcotic drugs is studied on the multi-wall carbon nanotube with the spectrophotometer. The amount of adsorption in various concentrations was calculated and its related diagram was drawn. The result, which was obtained by Langmuir, Freundlich and Temkin in 296 ± 2 K, compared coefficient parameters show that the Temkin has the most accordance.